(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In the present world, leaders are expected to nurture an environment of collaborative creativity and innovation for bringing transformation in the lives of the people. Creativity can be enhanced through spirituality as both have common values like curiosity, openness to experience, serendipity, patience, flow and happiness, humility, etc. The paper discusses their role and relevance in the context of positive leadership and illuminates the role of subtle mind in context of creativity and spirituality.